2010
DOI: 10.1371/journal.pone.0014051
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Tracing of Lamellocytes Demonstrates Drosophila Macrophage Plasticity

Abstract: Leukocyte-like cells called hemocytes have key functions in Drosophila innate immunity. Three hemocyte types occur: plasmatocytes, crystal cells, and lamellocytes. In the absence of qimmune challenge, plasmatocytes are the predominant hemocyte type detected, while crystal cells and lamellocytes are rare. However, upon infestation by parasitic wasps, or in melanotic mutant strains, large numbers of lamellocytes differentiate and encapsulate material recognized as “non-self”. Current models speculate that lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 47 publications
(93 reference statements)
7
104
0
1
Order By: Relevance
“…Many studies established that plasmatocytes and lamellocytes follow specific differentiation pathways (Lanot et al, 2001;Sorrentino et al, 2002Sorrentino et al, , 2004Meister, 2004;Crozatier et al, 2004;Krzemień et al, 2007). However, recent works on Drosophila hemocytes lineage showed that plasmatocytes could indeed differentiate into lamellocytes (Honti et al, 2010;Avet-Rochex et al, 2010;Stofanko et al, 2010). Despite lamellocytes having long been considered the major hemocyte type forming the bulk of capsules in Drosophila (Brehélin and Duvic, 1999), we have shown that not all Drosophila species actually possess this cell type (Eslin and Doury, 2006;Eslin et al, 2009;Havard et al, 2009).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many studies established that plasmatocytes and lamellocytes follow specific differentiation pathways (Lanot et al, 2001;Sorrentino et al, 2002Sorrentino et al, , 2004Meister, 2004;Crozatier et al, 2004;Krzemień et al, 2007). However, recent works on Drosophila hemocytes lineage showed that plasmatocytes could indeed differentiate into lamellocytes (Honti et al, 2010;Avet-Rochex et al, 2010;Stofanko et al, 2010). Despite lamellocytes having long been considered the major hemocyte type forming the bulk of capsules in Drosophila (Brehélin and Duvic, 1999), we have shown that not all Drosophila species actually possess this cell type (Eslin and Doury, 2006;Eslin et al, 2009;Havard et al, 2009).…”
Section: Introductionmentioning
confidence: 60%
“…Later Lanot et al (2001) suggested that podocytes would be puparian macrophages involved in phagocytosis of larval histolytic tissues while for the last decade, it was established that lamellocytes' differentiation follows a particular pathway which takes place in the Drosophila larvae lymph glands or in subepidermal populations of sessile hemocytes (Márkus et al, 2009). Recent works brought new insights supporting the hypothesis of lamellocytes differentiation from plasmatocytes (Stofanko et al, 2010). Cell lineage analysis demonstrated that embryo-derived plasmatocytes can differentiate into lamellocytes in response to a genetic mutation (Avet-Rochex et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, small RNA-seq was conducted at 0 h, 3 h (early response), and 48 h (late response) after treatment with ecdysone, and protein levels determined by label-free quantitative mass spectrometry at 0 and 48 h. We have previously characterized the mRNA dynamics at 0, 3, and 48 h that we consider here in our analysis (Wood et al 2011). Transcriptional profiling studies suggest that Drosophila Kc167 cells are plasmatocytes (Cherbas et al 2011), a subclass of hemocytes involved in immune surveillance that may further differentiate into lamellocytes, podocytes, or macrophages (Stofanko et al 2010). To examine whether ecdysone tRNA levels and protein translation www.rnajournal.org 1809 treatment has an effect on the differentiation state of Kc167 cells, we analyzed expression markers for these relevant cell types at 0, 3, and 48 h. Up-regulation of Croquemort, a macrophage receptor for apoptotic cells (Franc et al 1996(Franc et al , 1999, Singed (Fascin), an actin-bundling protein important for macrophage migration (Zanet et al 2012), and Schnurri, previously shown to regulate hemocyte-to-macrophage differentiation (Kelsey et al 2012), together suggest that ecdysone induces plasmatocyte-to-macrophage differentiation in this cell line (Fig.…”
Section: Transcriptional and Proteomic Response To Steroidhormone Sigmentioning
confidence: 99%
“…Although the GOF JAK allele hop Tuml has been widely studied (Bina et al, 2010;Harrison et al, 1995;Kwon et al, 2008;Stofanko et al, 2010), a second GOF HOP allele mutated in its JH2 pseudokinase domain and called hop T42 , has also been identified (Luo et al, 1997). Given the key significance of the human JAK2 V617F pseudokinase domain mutation in MPNs, we also assessed the tumour burden in hop T42 heterozygous adults with genetic backgrounds reducing stat92E or Ga73B levels ( Fig.…”
Section: Ga73b Promotes Tumorigenesismentioning
confidence: 99%